Metformina na gestação: reflexão à luz da literatura e seu uso no hospital das clínicas da UFMG - Aline Costa Calixto (2017)
Introduction: The incidence of diabetes in pregnancy increases worldwide. Glycemic uncontrol can trigger unfavorable maternal, fetal and neonatal outcomes. When the initial treatment with physical activity and hypocaloric diet fails, pharmacological measures are insulin and / or oral hypoglycemic agents. The use of insulin is widely diffused and accepted in the clinical setting. Oral hypoglycemic agents, such as metformin, used more timidly, show promising results in the scientific setting. Objective: To understand and reflect on the use of metformin during pregnancy in the HC-UFMG high-risk prenatal service, comparing it to the literature. Patients and methods: Follow-up of diabetic pregnant women at the HC-UFMG endocrinology clinic, who used metformin between December 2015 and June 2016. Results and discussion: A total of seven patients had been indicated for the use of metformin during pregnancy. The findings followed a trend described in the literature. Most of the diabetic pregnants arrive at HC-UFMG with metformin of previous use suspended by the service of origin. Patients in the study had insulin resistance prior to gestation and had already taken metformin. No patient presented side effects, following a trend described in the literature that, when present, and usually gastrointestinal, these effects disappear along the time of use. Professionals are often safer with the introduction of metformin after evidence of normal fetal morphology on ultrasound. The oral use of metformin is better received by the patient than the injectable application of insulin. The study's glycemic controls succeeded in bringing the patients to term or until another associated comorbidity determined the need for early delivery, such as pre-eclampsia. Weight gain during pregnancy was in most cases within the recommended range considering pre-gestational BMI. Conclusion: The literature states that metformin during pregnancy is safe for the mother-fetus binomial in the short term and is effective. Despite this, metformin is still rarely used in prenatal services in Brazil, even in HCUFMG. It is recommended that there be integration between services of assistance to pregnant women, with contact of the basic network with updates on metformin practiced in the specialized network. The tendency of developed countries is to regulate such a patient-friendly drug, safely on prescription, administration and control of glycemic effects, as well as better transportation and storage logistics. It is urgent to carry out Brazilian clinical studies that support the widespread use of metformin in pregnancy.